Resource Management for Heterogeneous Networks in LTE Systems - Hu, Rose Qingyang; Qian, Yi.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This SpringerBrief provides an in-depth look at the key issues that affect the performance of heterogeneous networks and presents schemes that can effectively tackle these issues. In particular, this book discusses unbalanced traffic load among the macro and micro Base Stations (BSs) caused by the transmit power disparity, and a load-balancing based mobile association scheme to balance the traffic load among the macro and micro BSs. This book also introduces a fractional frequency reuse (FFR) scheme with proper power control to help reduce interference at the UEs which are most vulnerable to such intra-cell interference. The last section investigates radio resource allocation issues for heterogeneous networks with cooperative relays, and proposes a resource allocation framework that could achieve proportional fairness among the UEs. Numerical results are provided to demonstrate the effectiveness of the proposed solutions in tackling the problem and improving network performance. Resource Management for Heterogeneous Networks in LTE-A Systems is designed for researchers and professionals working in networking and resource management. The content is also valuable for advanced-level students in computer science and electrical engineering.
Introduction -- Heterogeneous Network Model and Preliminaries -- Mobile Association for Heterogeneous Networks -- Interference Management in Heterogeneous Networks with Fractional Frequency Reuse -- Radio Resource Allocation in Heterogeneous Networks.
Keywords: Electrical engineering; Computer communication systems; Power electronics; Application software; Communications Engineering, Networks; Computer Communication Networks; Power Electronics, Electrical Machines and Networks; Information Systems Applications (incl. Internet).